Integrating digital technologies in agriculture for climate change adaptation and mitigation: state of the art and future perspectives - Parra-López, Carlos; Ben Abdallah, Saker; Garcia-Garcia, Guillermo; Hassoun, Abdo; Sánchez-Zamora, Pedro; Trollman, Hana; Jagtap, Sandeep; Carmona-Torres, Carmen (Elsevier, 2024)
Agriculture faces a major challenge in meeting the world's growing demand for food in a sustainable manner in the face of increasing environmental pressures, in particular the growing impact of climate change. Agriculture is also a major contributor to climate change. Digital technologies in agriculture can contribute to climate change adaptation and mitigation. This paper examines the interactions between climate change and agriculture, reviews adaptation and mitigation strategies, explores the application of digital technologies in this context, and discusses future challenges and opportunities for sustainable and resilient agriculture. The final aim is to provide a comprehensive overview of the current state and future prospects of digital agriculture in the context of climate change. A comprehensive literature review was conducted on adaptation and mitigation strategies in agriculture, and on the current state and future prospects of digital agriculture in the context of climate change adaptation and mitigation. The identified applications of digital technologies in agriculture include Remote Sensing for crop monitoring, Big Data for predictive modelling of water shortages and pest outbreaks, Artificial Intelligence for pest identification and tracking, the Internet of Things for precision fertiliser management, nanotechnology for soil improvement, robots for targeted spraying, and blockchain for improved soil management and supply chain transparency, among others. These technologies facilitate the precise management of resources, improve decision-making processes and enable more efficient agricultural practices. Digital technologies also help mitigate climate change by optimising inputs such as water and fertiliser, thereby reducing greenhouse gas emissions and promoting carbon sequestration. However, there are significant barriers to the adoption of these technologies, including the digital divide, high up-front costs and complexity, as well as privacy and security concerns and the environmental impact of technology use. Future action must address these barriers by investing in infrastructure and training, ensuring financial incentives, developing scalable digital solutions tailored to local agricultural conditions, increasing digital literacy among farmers, developing comprehensive governance frameworks, and exploring the integration of multiple digital technologies. The paper contributes to advancing scientific understanding and guiding practice and policy towards sustainable agriculture in the face of climate change. It provides a call to action for a more sustainable future in the context of climate change and highlights the urgency of multi-stakeholder collaboration to create an enabling environment for the widespread adoption of these innovations, ensuring that they are accessible, cost-effective and suitable for different farming environments.
Keywords: Agriculture 4.0; Climate change; Digital transformation; Digitalisation; Sustainability; 30 Agricultural, Veterinary and Food Sciences; 46 Information and Computing Sciences; 40 Engineering; 13 Climate Action; 2 Zero Hunger; Agronomy & Agriculture